A base-free synthetic route to anti-bimetallic lanthanide pentalene complexes. Issue 17 (5th January 2017) - Kilpatrick, Alexander F. R.; Cloke, F. Geoffrey N.
Abstract : Homobimetallic complexes of Yb, Eu and Sm bridged by a silylated pentalene ligand have been prepared and intermetallic communication studied by magnetic measurements and cyclic voltammetry. Abstract : We report the synthesis and structural characterisation of three homobimetallic complexes featuring divalent lanthanide metals (Ln = Yb, Eu and Sm) bridged by the silylated pentalene ligand [1, 4-{Si i Pr3 }2 C8 H4 ] 2− (= Pn † ). Magnetic measurements and cyclic voltammetry have been used to investigate the extent of intermetallic communication in these systems, in the context of molecular models for organolanthanide based conducting materials.